Annual plant reviews, Volume 31: Plant mitochondria - Logan, David C (Blackwell, 2012)
Mitochondria are critical organelles in the metabolic regulation of almost all eukaryotic organisms. Knowledge of their biochemistry and molecular biology in plants has been fuelled over recent years by the rapid progress made in genome sequencing and the ability to manipulate gene expression.